Practical Challenges and Pitfalls of Bluetooth Mesh Data Collection Experiments with ESP32 Microcontrollers - V., Marcelo Paulon J.; Souza, Bruno José Olivieri De; Lamenza, Thiago de Souza; Endler, Markus (Anais do Latin-American Symposium on Dependable Computing (LADC); 2024: Anais do XIII Latin-American Symposium on Dependable Computing, 2024)
Testing network algorithms in physical environments using real hardware is essential to reduce the gap between theory and practice in the field and is an exciting way to explore technologies such as Bluetooth Mesh. We implemented a Bluetooth Mesh data collection strategy and deployed it in indoor and outdoor settings using ESP32 microcontrollers. We also implemented an alternative packet routing mechanism based on Bluetooth Mesh - MAM, which has already been discussed and simulated in previous work using the OMNET++ simulator. We compared the real-world ESP32 experiments with the past simulations, and the results differed significantly: the simulations predicted a +459% unique message collection compared to the results we obtained with the ESP32. MAM performed better than Bluetooth Mesh’s default relay strategy, with up to +4.06% more (unique) data messages collected. Based on this practical experience, we also identified vast room for improvement in our ESP32 mesh implementation, including improving memory efficiency and building better tooling for conducting outdoor experiments. We also discuss multiple challenges we experienced when implementing, deploying, and running benchmarks using Bluetooth Mesh and the ESP32 platform.